2006
DOI: 10.1590/s0100-55022006000200005
|View full text |Cite
|
Sign up to set email alerts
|

Animais em aulas práticas: podemos substituí-los com a mesma qualidade de ensino?

Abstract: Com o objetivo de verificar a possibilidade de substituição de animais em aulas práticas, comparou-se o grau de aprendizagem entre duas turmas do curso de Medicina submetidas a aulas distintas, com e sem o uso de animais. Foram verificados, também, os sentimentos despertados pela presença destes animais. Os alunos ingressantes do curso de Medicina foram divididos em dois grupos, estabelecendo-se dois protocolos de aulas práticas, um deles com animais de laboratório e outro sem. O assunto, comum às duas aulas, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
43

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 5 publications
1
10
0
43
Order By: Relevance
“…This research showed a significant reduction in the use of animals in educational procedures, highlighting the growing preference for alternative methods. These data corroborate a previous review by Diniz et al 15 , who found out that only 1% of the total number of animals involved in protocols evaluated by the CEUA were used for educational procedures. However, it was not possible to find in the national literature a study that evaluated the tendency to use animal protection procedures caused by the influence of the CEUA.…”
Section: The Impact Of An Ethics Committee On Animal Protectionsupporting
confidence: 91%
“…This research showed a significant reduction in the use of animals in educational procedures, highlighting the growing preference for alternative methods. These data corroborate a previous review by Diniz et al 15 , who found out that only 1% of the total number of animals involved in protocols evaluated by the CEUA were used for educational procedures. However, it was not possible to find in the national literature a study that evaluated the tendency to use animal protection procedures caused by the influence of the CEUA.…”
Section: The Impact Of An Ethics Committee On Animal Protectionsupporting
confidence: 91%
“…Nas publicações acadêmicas analisadas, o vegetarianismo tem sido vinculado principalmente à ética abolicionista, ampliando a contribuição do vegetariano de mero avaliador dos efeitos da dieta na saúde humana para a reflexão a respeito dos motivos e consequências do atual sistema de produção animal, acrescendo a comparação com outras utilizações, como para finalidade científica, cuja normatização vem sendo consolidada há mais tempo (Diniz et al, 2006;Feijó et al, 2008;Lima et al, 2008;Hill, 2011). Provavelmente a visão antropocêntrica e utilitarista torna a sociedade mais tolerante à produção animal para alimentação, mesmo tendo aumentado em cinco vezes o número de animais expostos às condições artificiais e estressantes de confinamento e manejo (Bezerra et al, 2007, Singer e Mason, 2007.…”
Section: Discussionunclassified
“…These studies provide evidence that students using alternative methods learn equally well, or sometimes better, than those using laboratory animals (2,4,6,17). In fact, teaching models that do not involve harmful animal experimentation or death during class seem to be beneficial to student learning (18).…”
Section: Discussionmentioning
confidence: 99%